Analisis Implementasi Kebijakan Kantong Plastik Berbayar di Ritel Modern Banda Aceh - Bahagia Bahagia; Irda Yunita; Riezky Marlia Susanti (Fakultas Teknik, 2019)
One of the efforts to reduce plastic waste is as noted by the Ministry of Environment and Forestry issued Circular Number S.1230 / PSLB3-PS / 2016 concerning Reduction of Plastic Waste through Paying for Plastic Bags Paid in all modern retail market outlets in Indonesia. The purpose of this study is to find out how the response of consumers shopping at Suzuya Mall Banda Aceh based on internal and external factors on the implementation of paid plastic bags. The research method used in this study is the SWOT analysis method. The results showed that the internal strategy factor with the highest strength was 3.39 which was to reduce the use of plastic bags in the environment. While the highest weakness value of 2.88 was applied only to retail stores and considered not comprehensive. The external strategy factor with the highest opportunity value of 3.51 was giving an opportunity to producers in an environmentally friendly bag craft business.